Antimicrobial neuropeptides and their therapeutic potential in vertebrate brain infectious disease - Li, Xiaoke; Chen, Kaiqi; Liu, Ruonan; Zheng, Zhaodi; Hou, Xitan (Frontiers in Immunology, 2024)
The defense mechanisms of the vertebrate brain against infections are at the forefront of immunological studies. Unlike other body parts, the brain not only fends off pathogenic infections but also minimizes the risk of self-damage from immune cell induced inflammation. Some neuropeptides produced by either nerve or immune cells share remarkable similarities with antimicrobial peptides (AMPs) in terms of size, structure, amino acid composition, amphiphilicity, and net cationic charge. These similarities extend to a wide range of antibacterial activities demonstrated in vitro, effectively protecting nerve tissue from microbial threats. This review systematically examines 12 neuropeptides, pituitary adenylate cyclase-activating peptide (PACAP), vasoactive intestinal peptide (VIP), α-melanocyte stimulating hormone (α-MSH), orexin-B (ORXB), ghrelin, substance P (SP), adrenomedullin (AM), calcitonin-gene related peptide (CGRP), urocortin-II (UCN II), neuropeptide Y (NPY), NDA-1, and catestatin (CST), identified for their antimicrobial properties, summarizing their structural features, antimicrobial effectiveness, and action mechanisms. Importantly, the majority of these antimicrobial neuropeptides (9 out of 12) also possess significant anti-inflammatory properties, potentially playing a key role in preserving immune tolerance in various disorders. However, the connection between this anti-inflammatory property and the brain’s infection defense strategy has rarely been explored. Our review suggests that the combined antimicrobial and anti-inflammatory actions of neuropeptides could be integral to the brain’s defense strategy against pathogens, marking an exciting direction for future research.